Unilateral Idiopathic Calcinosis Cutis: A Case Report - Fahad Alsaif; Amr M. Abduljabbar (Karger Publishers, 2017)
Calcinosis cutis is a rare disorder characterized by the deposition of calcium in the skin and subcutaneous tissue. Unilateral idiopathic calcinosis cutis has only rarely been reported in the literature. Here, we report the case of a 7-year-old healthy girl who presented with multiple asymptomatic hard nodules on the right side of her body. Histopathological, radiological, and extensive blood investigations confirmed the diagnosis of unilateral idiopathic calcinosis cutis.